STATUS TANAH ULAYAT ATAS HAK GUNA USAHA YANG TELAH BERAKHIR (BERDASARKAN PERATURAN PEMERINTAH NOMOR 18 TAHUN 2021) - Tamarine Camalia; Taupiqqurrahman (Fakultas Hukum Universitas Muhammadiyah Sumatera Utara, 2021)
The transition of the status of the ulayat land from the land use rights on it is a polemic that currently needs to be discussed, especially if it triggers a land dispute between the two in the future. In this case, it is about the status of ulayat land if the use rights bound on it have expired. The differences in the time limits in the regulations have dissimilarities, giving rise to different perceptions. The purpose of this paper is to analyze ulayat land, land tenure, and usufructuary rights to clarify the status of ulayat land in the end. With qualitative descriptive methods and secondary data in the form of Literature Studies and Legislations, the results of the discussion obtained are Cultivation Rights which have expired, if the land used island that has previous customary rights, then the land returns to customary land managed by the community. Indeed, in government regulation number 18 of 2021 it is stated that the land will be turned into state land, however, what is meant is if the management rights were previously used for public needs or the interests of the state.